Analisis Persediaan Suku Cadang Kritis Dan Reliabilitas Mesin Water Injection Pump di PT. Pertamina EP UBEP Jambi - Faizal Rahman; Samsir '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This Study was conducted at PT. Pertamina EP located at Jakarta in order to analyze reliability of machines that used in that company. This study is to suggest the company the picture of the aspect that still inefficient in the operational system. This study is using prime and secondary data with water injection pump type GASO 3364-7 as the study object that located in business, explorations and production unit (UBEP) Jambi. the data is collected from spare part changes within 2011-2012 period. Using ABC analysis, the critical parts within the machines will be sorted out and each of the critical parts will be measured the mean time between failure with comparing the total uptime of the spare part and total breakdown per critical component in that period of time. As the result of the study, can be concluded that water injection pump machine, with 3 month averages will have a breakdown that involving the critical parts. The recommendation is, the management has to pay attention at the inventory level of critical parts so it can be more efficient where is the inventory level is not bigger than usage level considering critical parts have high price above all parts that will make higher inventory cost if the supply is more than usage and lack of inventory will causing major shutdown that will cost company some costly opportunity.Keywords : Reliability, Maintenance.